The effects of parental control and warmth on problematic internet use in adolescents: A prospective cohort study - Lukavská, Katerina; Vacek, Jaroslav; Gabrhelík, Roman (Journal of behavioral addictions, 2020)
BACKGROUND AND AIMS: Problematic internet use (PIU) is a highly prevalent condition with severe adverse effects. The literature suggests that parent-child bonding and parental behavioral control exert protective effects against PIU. However, the most relevant studies rely on simplistic measurement of parenting, cross-sectional designs and mixed-aged samples. Our study analyzed the effect of maternal and paternal parenting on PIU by using a prospective design and a cohort sample of same-aged children. METHODS: Data from 1,019 Czech 12-year-old sixth-graders who were followed until ninth grade were used. Maternal and paternal responsiveness and strictness were reported by children using the Parental Acceptance-Rejection Questionnaire (PARQ) and the Parental Control Scale (PCS). PIU was measured by the Excessive Internet Use Scale (EIUS). RESULTS: The self-reported PIU prevalence in nine-graders (15-year-old) was 8.1%. Parenting, reported by adolescents 18 months before PIU screening, showed significant relationships with PIU: parental responsiveness was negatively and moderately associated, while maternal strictness showed a weak positive association; the authoritative parenting style in both parents decreased PIU, with a PIU probability of 3.21%, while a combination of maternal authoritarian and paternal neglectful parenting was associated with PIU probability as high as 20.9%. DISCUSSION AND CONCLUSIONS: The self-reported prevalence of PIU in Czech adolescents was found to be high. The effects of parenting on PIU were similar to the effects of parenting on other problematic behavior among adolescents. Our findings showed the need for interventions to prevent PIU by helping parents to apply optimal parenting styles.
Keywords: Internet Addiction Disorder; vztahy mezi rodiči a dětmi; chování mladistvých; mladiství; Česká republika; mužské pohlaví; problematic use of internet; Prospective Studies; rodičovství; Czech Republic; dítě; Child; ženské pohlaví; Humans; prospektivní studie; parental warmth; Adolescent Behavior; Parent-Child Relations; internet addiction; adolescence; parental control; parenting styles; Parenting; Female; Adolescent; netholismus; lidé; Male